Reversible luminescence modulation of Ho‐doped K0.5Na0.5NbO3 piezoelectrics with high luminescence contrast. Issue 6 (26th December 2017) - Zhang, Yao; Liu, Jian; Sun, Haiqin; Peng, Dengfeng; Li, Ruihong; Bulin, Chaoke; Wang, Xusheng; Zhang, Qiwei; Hao, Xihong
Abstract: A significant luminescence modulation behavior based on photochromic reactions was observed in Ho 3+ ‐doped (Na0.52 K0.48 )0.92 Li0.08 NbO3 ceramics, fabricated by the conventional solid‐state reaction method. Under visible light irradiation (407 nm) for 20 second, the samples changed pale gray from initial pale green, and returned to their original color by a thermal stimulus of 230°C for 10 minutes, showing typical photochromic phenomenon. Under 453 nm excitation, the samples exhibited strong green emission at 551 nm. Interestingly, their green emission intensity can be effectively tailored by controlling photochromic reaction processes (irradiation wavelength and time), and the luminescent modulation ratio (Δ R t ) reaches up to 77%. And, the Δ R t value has no any obvious degradation after 10 cycles by alternating visible light irradiation and thermal stimulus, showing excellent reversibility. These results make it potential applications in many fields as a kind of multifunctional material.